The impact of building material on thermal performance of residential bulding in tropical climate / Nor Jannah Muhd Satar - Muhd Satar, Nor Jannah (2008)
The residential buildings in Malaysia are not thermally comfortable due to climate, building design, building materials and energy consumption. This study was carried out to evaluate the impact of construction material on thermal performance in residential building. The objectives for this study are to measure the thermal environmental data of residential building at tropical rainforest of Taman Negara Pahang, to measure the thermal environmental data of residential building with conventional construction at urban area of Shah Alam and rural area of Pendang Kedah, and to analyze and compare the impact of building materials on selected residential building. Nine houses were taken as a sample. There are two conventional construction of heavyweight house at Bukit Jelutong, two heavy weights and one lightweight house at Taman Negara, and two mix weights, one heavyweight and one lightweight house at Pendang. Data were logged using data logging equipments. Some data were collected consecutively and some data were collected simultaneously. Data were analyzed for temperature, temperature difference, relative humidity, light intensity, thermal comfort hours and decrement factor. In conclusion, findings show that lightweight residential building is hotter up to 1.9 °C during day time and cooler up to 0.9 °C during night time. Heavyweight residential building recorded different affect that is the house is cooler during day time and hotter during night time.